0005 From recovery to resus – developing an in-situ simulation collaboration. (2nd November 2015) - Woodier, Nick; Dowling, Myles; Gill, Steven; Minhas, Honeyia; Mole, Jonathan; Linford, Sarah; Saule, Ieva; Barrow, Clare; Beer, Thea De; Coffey, Frank; Baxendale, Bryn
Abstract : Background/context: High-fidelity simulations are educationally effective, 1 improve patient outcomes 2 and reduce mortality 3 through team training. In-situ simulation allows the practice of team skills and behaviours in actual clinical settings. This not only enhances learning through active experimentation 4 in the "real-world, " but also allows assessment of system efficacy. This can identify latent issues for change to enhance safety of care for patients. In-situ simulation is typically undertaken in one setting at a time. We describe our collaboration undertaking simultaneous in-situ simulations across three settings. Methodology (used): Through collaboration between the Departments of Anaesthesia, Critical Care and Emergency Medicine and supported by the Trent Simulation and Clinical Skills Centre, we piloted three simultaneous in-situ simulations. These took place in Resus (spontaneous intracranial bleed), Obstetric Theatres (dropping GCS during labour) and Theatre Recovery (post-op patient requiring transfer). Mixed-ability anaesthetic participants rotated around simulations working with local teams. Participants were debriefed after each scenario and feedback sought. Results/outcomes (recorded to date): This pilot highlighted the benefits of specialties collaborating to deliver multiple in-situ simulations. All participants (12 responders) described an excellent opinion of the scenarios highlighting that the simulations built relationships and clarified roles in each setting. Also a number of latent issues were discovered, particularly in the Emergency Department. These included the availability of equipment, communication issues and environmental design. Potential impact: This was the first in a series of collaborative in-situ simulations planned locally. They have the potential to: Improve team training across specialties to enhance role recognition and accountability Improve system performance by identifying latent issues to address, and resilience factors to enhance Future goals include designing the simulations to follow the same patient through different areas in the hospital. References: Issenberg SB, McGaghie WC, Petrusa ER, et al . Features and uses of high-ﬁdelity medical simulations that lead to effective learning. Med Teach 2005;27:10–28 Boet S, Bould MD, Fung L, et al . Transfer of learning and patient outcome in simulated crisis resource management: a systematic review. Can J Anaesthesia 2014;61(6):571–582 Neily J, Mills PD, Young-Xu Y, et al . Association between implementation of a medical team training program and surgical mortality. JAMA 2010;304(15):1693–700 Kolb D, Fry R. Toward an applied theory of experiential learning . London: John Wiley, 1975